R-Cu magnetic coupling in RBa2Cu3O6+x, with particular reference to PrBa2Cu3O6+x - Boothroyd, A (1997)
In this paper I enumerate the possible magnetic structures that may be observed in RBa2Cu3O6+x compounds when a bilinear coupling exists between the R and Cu magnetic moments. I discuss the implications of this coupling for local relaxation probes at the R site. (C) 1998 Elsevier Science B.V. All rights reserved.